Analisis Pada Penyelesaian Analisis Kompleks: Curiosity Attitude Mahasiswa - Aulia Sthephani; Fitriana Yolanda (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This research aims to describe and describe curiosity student. The indicators of curiosity in this study are asking about information or problems given, reading sources outside the textbook about material related to the lesson, the desire to learn, and the desire to solve problems. The subjects of this research were students of the FKIP UIR mathematics education study program for the 2019/2020 academic year which consisted of 60 people. This research was conducted from April 2020 to July 2020. The research method used was descriptive qualitative. Retrieval of data using a curiosity questionnaire instrument at the completion of the complex analysis that has been developed by the researcher. The data analysis technique used was qualitative questionnaire data analysis. The results of data analysis show that overall the curiosity is students'classified as "good" with an average questionnaire score of 75.19%, this indicates that there is curiosity of students towards solving complex analyzes, but it still needs to be improved through learning that can increase student curiosity.